ANALISIS PERMINTAAN TABUNGAN TARBIYAH PADA BANK PT. BPRS BERKAH DAN FADHLILLAH DI BANGKINANG O - Raidhatul Hasana; Syapsan Syapsan; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the analysis of income and profit sharing of the amount of costomer saving, to find out the reason people do tarbiyah savings and to know the most dominant factor to the amount of savings in PT. BPRS Bangkinang. This study uses secondary data obtained from BPS in Bangkinang ana primary data obtained from savings costomer respondents on PT. BPRS Bangkinang. The population in this research is tarbiyah saving costomer at PT. BPRS in Bangkinang and respondents in this study amounted to 50 customers.This study uses purposive random sampling technique in determining the sample, this technique is used for certain considerations and obtained 50 customers tarbiyah saving that chose to save in PT. BPRS Bangkinang using questionnaire and interview techniques. Furthermore, the analytical techniques in which the stages of data presentation, and withdrawal of conclusions.From the results of this study obtained income factor is not a factor that determines the customer savings tarbiyah choose to save money in the bank PT. BPRS in Bangkinang, this is evidenced from the result of the questionnaire that l have distributed to the respondents. While the profit-sharing factor becomes a factor that determines the customer chooses the bank PT. BPRS Bangkinang, this is proven not many respondents who know what is the ratio of deal by reaching 80% or 40 people from 50 people. Not many respondents who know what is the ratio of deal by reaching 80% or 40 people from 50 people.Keywords :Demand Analysis, Saving Tarbiyah, Bank BPRS